Penatalaksanaan Perawatan Saluran Akar Pada Gigi 11 dan Restorasi Porcelain Fused to Metal Crown dengan Custom-made Metal Post and Core - Karina Nabilla; Reni Nofika (Andalas Dental Journal, 2019)
Dental caies almost infected the pulp. The ernomous of cavity need core as the retention. This paper aimed to describe the management of dental caries to final restoration. A woman aged 22 yearscome to Dental Hospital with chief complain a discoloration on her restorated front teeth. Objective examination showed still vital but spontaneous dull pain recorded from patient. Root canal treatment then suggested with custom made post and core porcelain fused to metal crown as a final restoration.